Prevalence of Blastocystis hominis and Giardia lamblia Parasites in Patients of Four Regions in East – South Baghdad: Shatha Abdul Wahab Raof Nada Hatim Abdul-Rahman - Raof, Shatha Abdul Wahab (The Iraqi Journal of Veterinary Medicine, 2011)
A total of 250 stool specimens from patients live in Al-Ameen, Al-Mashtal, Al-Baladiyat and Al-Nahrawan, districts of Baghdad city were collected. The watery and loose specimens were wet mounted with normal saline and buffered methylene blue then all specimens concentrated and examined with Lugol’s iodine solution. The protozoal parasites of medical importance Blastocystis hominis and Giardia lamblia were respectively detected in 59 (24.6%) and 42 (17.5%), samples with mixed infection were in eight samples. Differences due to district lacked significance. Statistical significance was observed when the influence of age category was tested (P<0.05). The highest infestation percentage with both parasites was noticed in the 5 – 10 years category whereas the lowest percentage was in the 19 – above years category. Seasonal variations and sex of the infected patients with both protozoa did not reach statistical significance. Significant differences were observed between number of infected patients with B. hominis and G. lamblia in the age categories of respectively Al-Ameen and Al-Baladiyat districts. Significance was recorded in the differences between percentages of the age categories’ females as well as of the age category 5 – 10 years males and females that were infected with G. lamblia Similar significance marked the percentages of infection of both sexes with B hominis in the age categories